Innovative Use of Paddy Straw Ash in Concrete: Boosting Strength and Sustainability - , Satinder Kaur Khattra, Jaspal Singh, Ritesh Jain (Archives of Current Research International, 2025)
The increasing demand for sustainable building materials has prompted the use of agricultural waste products in concrete production. This paper explores the potential of using paddy straw ash (PSA), a by-product of rice farming, as a partial replacement for cement in concrete. The effects of various replacement levels of PSA on the compressive strength, durability and workability of concrete are evaluated. Compressive strength tests on mortar samples with varying PSA replacement levels (0–25%) revealed that optimal strength was achieved with 5–10% PSA substitution. The study demonstrates that PSA can improve the sustainability of concrete by enhancing its strength and reducing its environmental impact, while also making use of agricultural waste.